2013
DOI: 10.3402/jev.v2i0.20384
|View full text |Cite
|
Sign up to set email alerts
|

EVpedia: an integrated database of high‐throughput data for systemic analyses of extracellular vesicles

Abstract: Secretion of extracellular vesicles is a general cellular activity that spans the range from simple unicellular organisms (e.g. archaea; Gram-positive and Gram-negative bacteria) to complex multicellular ones, suggesting that this extracellular vesicle-mediated communication is evolutionarily conserved. Extracellular vesicles are spherical bilayered proteolipids with a mean diameter of 20–1,000 nm, which are known to contain various bioactive molecules including proteins, lipids, and nucleic acids. Here, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
345
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(353 citation statements)
references
References 23 publications
5
345
0
3
Order By: Relevance
“…Therefore, the subpopulation of CD9-single positive sEVs probably forms at the PM and early endocytic locations. described in sEVs (i.e., 100K pellets) secreted by mouse DCs (20) and other cells (21,22), and listed by us as components of "canonical exosomes" (23), but our results now show that only a restricted subset of these proteins represent sEV-specific markers, among which a subfraction is associated to tetraspaninenriched EVs corresponding to endosome-derived exosomes.…”
Section: Separation Of Sev Subtypes By Immuno-isolation With Antitetrmentioning
confidence: 65%
“…Therefore, the subpopulation of CD9-single positive sEVs probably forms at the PM and early endocytic locations. described in sEVs (i.e., 100K pellets) secreted by mouse DCs (20) and other cells (21,22), and listed by us as components of "canonical exosomes" (23), but our results now show that only a restricted subset of these proteins represent sEV-specific markers, among which a subfraction is associated to tetraspaninenriched EVs corresponding to endosome-derived exosomes.…”
Section: Separation Of Sev Subtypes By Immuno-isolation With Antitetrmentioning
confidence: 65%
“…Our previous work has shown that E. coliderived EVs induce systemic inflammation mimicking sepsis after entering the bloodstream (10) and that EVs from indoor dust and also from Staphylococcus aureus can induce neutrophilic pulmonary inflammation (11,12). In the current study, we hypothesized that EVs from Gram-negative bacteria, especially E. coli, are an important cause of neutrophilic inflammation and thereby emphysema in the lung.…”
mentioning
confidence: 87%
“…Lipid raft-associated proteins such as transferrin and caveolins, and other proteins involved in membrane trafficking, like the tetraspanins CD9, CD63, and CD81, which have been shown to bind to ESCRT machinery, are also enriched in exosomes [32][33][34]. There are now several databases that exist that list the assortment of materials that can be found in exosomes (Vesiclepedia, EVPedia, and Exocarta) [7,35,36].…”
Section: Exosome Biogenesismentioning
confidence: 99%